Modelling energy measurement data with annual duration lines - description of three options for practical use. (7th October 2022) - Knayer, Tobias; Kryvinska, Natalia
Energy data are necessary for successful planning and potential estimation. To characterise the temporal course, annual duration curves are used. They allow a graphical record and offer to compare the distribution of energy consumption. Often, these data are not available and entail great challenges for planners. Three ways of modelling an annual duration curve are shown. Procedure 1 works with measured data, procedure 2 with standard load profiles and monthly or annual consumption values. Procedure 3 shows how an estimate can be made without energy data. Most of the studies deal only with the generation of load profiles, but not of annual duration curves. Moreover, some work with complex mathematical functions and special software and consider only private households. There is no comparison with businesses or public buildings. The three options presented here are a simple estimation for a practical use to get a good and fast result.